Dissemination Program for Ancient Nusantara Manuscripts at the National Library of the Republic of Indonesia - Lumbantobing, Sarmianta; Samosir, Fransiska Timoria; Aliwijaya, Araf (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2026)
Background: Ancient Indonesian manuscripts serve as a vital repository of indigenous knowledge and cultural heritage. Despite their significance, empirical research into the collaborative dissemination frameworks required to transition these artifacts from archives to the public sphere remains limited. Purpose: This study investigates the dissemination programs for ancient manuscripts at the National Library of the Republic of Indonesia (Perpusnas RI), aiming to evaluate how these initiatives support manuscript preservation and active public utilization. Methods: Adopting a descriptive qualitative approach, the researchers conducted in-depth interviews with nine librarians and philologists, supplemented by direct and digital observations of social media and institutional websites. Data were transcribed using TurboScribe, manually coded, and validated through source and method triangulation. Analysis followed a rigorous process of reduction, presentation, and verification. Findings: The study identifies nine distinct dissemination channels: social media, the Khastara digital portal, physical exhibitions, webinars/workshops, Focus Group Discussions (FGDs), literacy classes, script-writing workshops, competitions, and podcasts. While these programs align with the Information Dissemination Systems (IDS) framework, the findings reveal a critical need for expanded social participation and institutional synergy. Originality/Value: Although Perpusnas RI has implemented a systematic dissemination infrastructure, the study highlights that cross-institutional collaboration remains the primary bottleneck. The research provides a strategic foundation for recommending a national collaborative model that integrates philologists, researchers, and local communities to ensure the sustainability of Indonesia’s manuscript heritage.